DURASI DAN PERUBAHAN HARGA DENGAN MARKOV CHAIN MONTE CARLO - , LILIH DEVA MARTIAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis proposed a model to analyze duration and price change of ultra high frequency data for an intraday transaction. This Price Change and Duration Model was decomposed in to four principal components, i.e. time duration between price changes, number of trades that result in no price change, direction of price change (up and down), and the size of price change. The last three components were the decomposition of price change itself. Parameter estimations of four components were calculated using Markov Chain Monte Carlo. The results of the study presents the values of parameter estimations for IBM data on 21st November 1990 that showed that there was no dynamic dependence in time duration and also there was some effect of duration in three variabels of price change.